2019
DOI: 10.9734/ajpas/2019/v5i230131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information and Communication Technology (ICT) in the Academic Performance of the University of Benin Post Graduate Students

Abstract: Student performance has several elements, but most significant is the role the information and communication technology plays. The performance of students in modern education is quite different from the traditional method used over the past decades. ICT is a revolution and has indeed bridged the divided world of information into single entity; it has further enhanced the resourcefulness of students in various academic institutions around the globe. This study is a fact finding into the role of ICT as it relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Data from the postgraduate students of the University of Benin (Uniben) revealed a substantial difference in academic activity between users and non-users of ICT facilities. Their findings demonstrated that ICT has a favorable influence on student performance (Osagie et al, 2019). Similarly, data analysis of graduate students in four programs of an education department at a northeastern U.S. university revealed that students were positive about the use of computers in their graduate work and utilized computers often for various academic objectives (Shaw and Giacquinta, 2000).…”
Section: Methods Samplingmentioning
confidence: 98%
“…Data from the postgraduate students of the University of Benin (Uniben) revealed a substantial difference in academic activity between users and non-users of ICT facilities. Their findings demonstrated that ICT has a favorable influence on student performance (Osagie et al, 2019). Similarly, data analysis of graduate students in four programs of an education department at a northeastern U.S. university revealed that students were positive about the use of computers in their graduate work and utilized computers often for various academic objectives (Shaw and Giacquinta, 2000).…”
Section: Methods Samplingmentioning
confidence: 98%
“…Thus, results as the bridging hub of all networks scattered worldwide. Networks of different kinds have different configurations with its operational scope based on the fundamental principle of the intended user [7]. The internal mechanism of the design structure of a network is usually not for public consumption and this is because there are inherent attributes of the security apparatus that prevent it from been hacked or accessed by unauthorised user [8].…”
Section: Introductionmentioning
confidence: 99%